Respuesta :

Answer:

J

Step-by-step explanation:

Find the common ratio r of the geometric sequence then multiply a term by r to obtain the next term

r = [tex]\frac{a_{2} }{a_{1} }[/tex] = [tex]\frac{6}{-36}[/tex] = - [tex]\frac{1}{6}[/tex]

The next 3 terms are

[tex]\frac{1}{6}[/tex] × - [tex]\frac{1}{6}[/tex] = - [tex]\frac{1}{36}[/tex]

- [tex]\frac{1}{36}[/tex] × - [tex]\frac{1}{6}[/tex] = [tex]\frac{1}{216}[/tex]

[tex]\frac{1}{216}[/tex] × - [tex]\frac{1}{6}[/tex] = - [tex]\frac{1}{1296}[/tex]

Answer:

J. [tex]-\frac{1}{36}[/tex], [tex]\frac{1}{216}[/tex], [tex]-\frac{1}{1296}[/tex]

Step-by-step explanation:

We are given the following geometric sequence and we are to find its 8th term:

[tex]-36, 6, -1, \frac{1}{6},...[/tex]

Here [tex]a_1=-36[/tex] and common ratio [tex](r) = \frac{-1}{6}=\frac{-1}{6}[/tex].

The formula we will use to find the next three terms is:

nth term = [tex]a_1 \times r^{(n-1)}[/tex]

5th term = [tex]-36 \times \frac{-1}{6}^{(5-1)}[/tex]  = [tex]-\frac{1}{36}[/tex]

6th term = [tex]-36 \times \frac{-1}{6}^{(6-1)}[/tex]  = [tex]\frac{1}{216}[/tex]

7th term = [tex]-36 \times \frac{-1}{6}^{(7-1)}[/tex]  = [tex]-\frac{1}{1296}[/tex]

ACCESS MORE